Modified activated carbon adsorbents, their preparation methods and applications

By growing ZIF-8 in situ on activated carbon and covalently bonding UiO-66-SO3H to form a composite structure, the problems of incomplete impurity removal and poor filler stability in the existing technology are solved, and efficient and simple n-octane purification is achieved to meet the high purity requirements.

CN122273482APending Publication Date: 2026-06-26FTSCI HUBEI BIOTECH CO LTD +3
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610462678.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-04-09
Publication Date
2026-06-26

AI Technical Summary

Technical Problem

Existing n-octane purification technologies suffer from incomplete impurity removal, poor packing stability, and complex preparation processes. Traditional activated carbon exhibits poor selectivity for adsorbing nonpolar aromatic hydrocarbons, molecular sieves struggle to efficiently capture metal ions, and MOFs particles are unevenly dispersed and prone to agglomeration, resulting in high pressure drop and rapid adsorption capacity decay.

Method used

ZIF-8 was grown in situ using activated carbon as a template, and then covalently bonded to UiO-66-SO3H through heat treatment to form a three-layer composite structure of activated carbon-ZIF-8-UiO-66-SO3H. The efficient removal of aromatic hydrocarbons, olefins and metal ions was achieved by utilizing the pore size screening of ZIF-8 and the sulfonic acid groups of UiO-66-SO3H. Combined with the macroporous structure of activated carbon, the preparation method is simple and regenerable.

Benefits of technology

It achieves efficient simultaneous removal of aromatic hydrocarbons, olefins and metal ions, meeting the high purity requirements of n-octane in high-end fields. The preparation process is simple, the adsorbent can be recycled, and the cost is reduced.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

This invention proposes a modified activated carbon adsorbent, its preparation method, and its applications. The modified activated carbon adsorbent is obtained by in-situ growth of ZIF-8 using activated carbon as a template, followed by covalent bonding of UiO-66-SO3H to form a three-layer composite structure of activated carbon-ZIF-8-UiO-66-SO3H. It utilizes the pore size of ZIF-8 to efficiently remove aromatic hydrocarbons and olefin impurities, while the sulfonic acid groups of UiO-66-SO3H achieve metal ion chelation and polar impurity capture. Combined with the macroporous structure of activated carbon, it ensures the removal of aromatic hydrocarbons, olefins, and metal ion impurities from n-octane. These components work synergistically to achieve high impurity removal efficiency. The modified activated carbon adsorbent has a simple preparation method, excellent regeneration performance, and can be recycled, showing significant application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of impurity removal adsorbent technology, specifically to modified activated carbon adsorbents, their preparation methods, and applications. Background Technology

[0002] As an important organic solvent, n-octane is widely used in high-end fields such as semiconductor manufacturing, precision electronic device cleaning, and photoresist dilution. These applications require extremely high purity of n-octane, especially the content of impurities such as aromatic hydrocarbons, alkenes, and trace metal ions must be controlled at extremely low levels (purity ≥ 99.99 wt%).

[0003] Currently, traditional techniques for purifying n-octane mainly employ activated carbon adsorption, molecular sieve separation, or a combination of both. However, these techniques have significant drawbacks: traditional activated carbon exhibits poor selectivity and limited removal efficiency for non-polar aromatic hydrocarbons, and has virtually no ability to capture trace metal ions; while molecular sieves possess some pore size sieving properties, their surfaces lack specific active sites, making it difficult to simultaneously achieve efficient removal of multiple types of impurities. Furthermore, existing composite packing materials are mostly prepared through stepwise loading, resulting in problems such as uneven particle dispersion, easy agglomeration, and weak binding force between metal-organic framework (MOF) materials and the support, leading to increased pressure drop and rapid decay of adsorption capacity during the purification process.

[0004] In recent years, MOFs have attracted widespread attention due to their unique porous structure and tunable functionality. ZIF-8 (zeolite imidazole ester framework material-8) possesses a regular microporous structure (pore size 0.34 nm) and excellent selective adsorption performance for aromatic hydrocarbons. Its π-π stacking can achieve efficient separation of C6–C8 aromatic hydrocarbons and olefins. Sulfonated UiO-66 (UiO-66-SO3H), as a functionalized derivative of zirconium-based MOFs, has strong acidic sulfonic acid sites, which can efficiently capture metal ions through acid-base neutralization and chelation. However, single MOF materials suffer from poor formability, high pressure drop, and difficulty in large-scale application. Combining them with activated carbon can fully leverage the advantages of both.

[0005] In existing technologies, the composite of activated carbon and MOFs often employs a two-stage loading or stepwise loading process, which suffers from problems such as complex preparation procedures, uneven MOF loading, and weak synergistic effects. Therefore, developing a composite filler with stable structure, synergistic function, simple preparation, and excellent regeneration performance, along with corresponding efficient purification equipment and methods, has become crucial for solving the problem of purifying high-purity n-octane. Summary of the Invention

[0006] The purpose of this invention is to overcome the shortcomings of existing n-octane purification technologies, such as incomplete impurity removal, poor packing stability, and complex preparation processes. This invention provides a method for the one-time and efficient removal of aromatic hydrocarbons, olefins, and metal ions from ZIF-8-sulfonated UiO-66 modified activated carbon and its preparation method, thereby meeting the high purity requirements of n-octane in high-end fields.

[0007] The technical solution of this invention is implemented as follows:

[0008] The first aspect of the present invention is to provide a modified activated carbon adsorbent, which is obtained by in-situ growth of ZIF-8 using activated carbon as a template, followed by covalent bonding with UiO-66-SO3H through heat treatment.

[0009] A second aspect of the present invention is to provide a method for preparing a modified activated carbon adsorbent, comprising:

[0010] S1. Use activated carbon to remove impurities from the surface;

[0011] S2. Disperse activated carbon, zinc source, and 2-methylimidazole into a solution, then add excess 2-methylimidazole; react at 50-70℃ for 1-3 hours to achieve in-situ growth of ZIF-8 using activated carbon as a template;

[0012] S3. Add zirconium source and 1,4-benzenedisulfonic acid to the system obtained in S2, treat at 70-85℃ for 3-5h to achieve covalent bonding of UiO-66-SO3H, and then filter.

[0013] S4. The filtered product is washed and dried to obtain a modified activated carbon adsorbent.

[0014] Furthermore, the activated carbon has a particle size of 20-40 mesh; and / or a specific surface area of ​​1000 m². 2 / g or more.

[0015] Further, in step S2, during solution dispersion, the ratio of activated carbon, zinc source, and 2-methylimidazole used during dispersion is 1g:(0.0002-0.0004)mol:(0.0015-0.003)mol;

[0016] And / or, the solution uses an alcohol as a solvent;

[0017] And / or, the excess amount of 2-methylimidazolium used is 3-5 times that of the zinc source.

[0018] Furthermore, the molar ratio of the zinc source to the zirconium source is (0.5-1.5):1.

[0019] Further, in step S3, the molar ratio of the zirconium source to 1,4-benzenedisulfonic acid is 1:(1.2-1.5).

[0020] A third aspect of the present invention is to provide the application of the modified activated carbon adsorbent described in the first aspect or the modified activated carbon adsorbent prepared by the preparation method described in the second aspect in the adsorption of impurities; wherein the impurities include at least one of aromatic hydrocarbons, olefins and metal ions.

[0021] Furthermore, the application is for the preparation of high-purity n-octane.

[0022] Furthermore, the application includes purifying and / or regenerating the modified activated carbon adsorbent, wherein the purification is performed by passing pure n-octane through the modified activated carbon adsorbent at a constant flow rate; and the regeneration is performed by first purging with nitrogen and then performing vacuum thermal desorption.

[0023] The purification process uses pure n-octane to simultaneously remove multiple impurities. The regeneration process preferably begins with purging with nitrogen at a flow rate of 3-5 BV / h for 1-2 hours to remove adsorbed organic impurities, followed by heating to 140-160℃, maintaining a vacuum of ≤10 kPa, and thermal desorption for 2-4 hours to remove chelated metal ions.

[0024] A fourth aspect of the present invention is to provide a method for preparing high-purity n-octane, comprising using the modified activated carbon adsorbent described in the first aspect or the modified activated carbon adsorbent prepared by the preparation method described in the second aspect, wherein crude n-octane is introduced at a constant flow rate into an adsorption unit filled with the modified activated carbon adsorbent, the temperature is controlled at 25-40°C, adsorption is carried out under a slight negative pressure condition, and the adsorbed n-octane is collected to obtain high-purity n-octane.

[0025] Furthermore, the crude n-octane refers to n-octane containing at least one impurity among aromatic hydrocarbons, olefins, and metal ions, and whose purity does not meet the requirements. It is preferably n-octane of industrial grade or above with a purity of 95.0% or higher, and n-octane with a purity of 99.99% or higher can be obtained.

[0026] Specifically, in some specific embodiments, the n-octane to be purified contains 10-200 ppm of aromatic hydrocarbon impurities (such as benzene), 10-100 ppm of olefin impurities (such as ethylene), and metal ions (Fe). 3+ Cu 2+ Mn 2+ (etc.) 20-60ppm, after adsorption by the modified activated carbon adsorbent described above, the removal rate of aromatic hydrocarbons can reach ≥98%, the removal rate of olefins can reach ≥96%, and the removal rate of metal ions can reach ≥99%.

[0027] Furthermore, the flow rate is 0.5-2 BV / h, preferably 0.5-1 BV / h, and more preferably 1 BV / h; the purpose of the slight negative pressure is to provide airflow power and improve the stability of adsorption, and it is preferably 0.05-0.1 MPa.

[0028] Compared with the prior art, the beneficial effects of the present invention are as follows: The modified activated carbon adsorbent of this invention uses activated carbon as a template to grow ZIF-8 in situ, and then covalently bonds UiO-66-SO3H to form a three-layer composite structure of activated carbon-ZIF-8-UiO-66-SO3H. The pore size of ZIF-8 is used to efficiently remove aromatic hydrocarbons and olefin impurities, while the sulfonic acid groups of UiO-66-SO3H achieve metal ion chelation and polar impurity capture. Combined with the macroporous structure of activated carbon, it ensures the removal of aromatic hydrocarbons, olefins and metal ion impurities in n-octane. The synergistic effect of these factors results in high impurity removal efficiency.

[0029] The modified activated carbon adsorbent described in this invention has a simple preparation method, excellent regeneration performance, and can be recycled, showing significant application prospects. Detailed Implementation

[0030] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0031] This invention provides a method for preparing modified activated carbon adsorbents using a one-time wet chemical co-precipitation process combined with low-temperature heat treatment. The specific steps are as follows: 1) Activated carbon pretreatment: Pulverize the activated carbon to 20-40 mesh, remove impurities, and dry it for later use to ensure its high specific surface area and unobstructed pores; 2) In-situ growth of ZIF-8: Activated carbon, Zn source and 2-methylimidazole are dissolved in methanol, ultrasonically dispersed and then an excess of ligand is added. The mixture is reacted at 50-70℃ for 1-3 hours to form ZIF-8 nanocrystals, which are then attached to the surface of activated carbon in situ. 3) Covalent bonding of UiO-66-SO3H: Add Zr source and 1,4-benzenedisulfonic acid, treat at 70-85℃ for 3-5h, and achieve covalent bonding of UiO-66-SO3H with activated carbon-ZIF-8 complex through low temperature heat treatment to avoid MOF particles falling off. 4) Post-processing: After washing and drying, the composite filler is obtained. This process does not require secondary seeding and achieves one-time molding.

[0032] The modified activated carbon adsorbent prepared by the above method can meet the requirements for simultaneous removal of multiple impurities. The specific mechanism is as follows: ①Through the pore size screening and π-π stacking of ZIF-8 and the sulfonic acid chelation of UiO-66-SO3H, aromatic hydrocarbons, olefins and metal ions are removed in one step, which can meet the requirement of ≥99.99wt% purity of n-octane after industrial-grade n-octane purification; ② Excellent synergistic performance: The mass ratio of ZIF-8 to UiO-66-SO3H in the adsorbent is optimized to 3:1~10:1, and activated carbon provides macroscopic pore structure. The three work together to achieve a balance between high adsorption capacity, low pressure drop and high flow rate. ③ Simple preparation process: A one-time wet chemical co-precipitation process is adopted to avoid the problem of uneven dispersion caused by step loading; ④ Good regeneration performance: The low-temperature regeneration process does not damage the material structure, can be recycled ≥15 times, and the adsorption capacity decay is ≤5%, reducing costs; a combination of "nitrogen blowing + vacuum thermal desorption" can be used to remove adsorbed organic impurities and metal ions under low-temperature conditions without damaging the MOFs structure and sulfonic acid active sites, realizing the recycling of filler. ⑤ Strong adaptability: The preparation method is simple and easy to use. It can achieve continuous purification and meet the needs of semiconductor, electronic device and other fields.

[0033] This invention also provides a high-purity n-octane purification device, comprising a column, composite packing material, a temperature / pressure sensor, and a closed-loop control system. 1) Column: Made of corrosion-resistant stainless steel, with an inner diameter of 2-5cm and a length of 10-30cm, and inlet and outlet pipes and sealing devices at both ends; 2) Composite filler: Modified activated carbon adsorbent obtained by the aforementioned preparation method; 3) Temperature / pressure sensors: installed at the inlet and outlet of the column respectively, for real-time monitoring of fluid temperature, pressure, purity and metal ions (detection of aromatic hydrocarbon / olefin content by gas chromatography and metal ion content by ICPMS).

[0034] In a preferred embodiment, the purification device is used as follows: the temperature is controlled at 25-40°C, crude n-octane is introduced into the column inlet under a slight negative pressure for adsorption, and the adsorbed n-octane is collected from the outlet to obtain high-purity n-octane.

[0035] In a preferred embodiment, the crude n-octane refers to n-octane containing at least one impurity among aromatic hydrocarbons, olefins and metal ions, and whose purity does not meet the requirements. It is preferably n-octane of industrial grade or above with a purity of 95.0% or higher, and n-octane with a purity of 99.99% or higher can be obtained.

[0036] Specifically, in some specific embodiments, the n-octane to be purified contains 10-200 ppm of aromatic hydrocarbon impurities (such as benzene), 10-100 ppm of olefin impurities (such as ethylene), and metal ions (Fe). 3+ Cu 2+ Mn 2+ (etc.) 20-60ppm, after adsorption by the modified activated carbon adsorbent described above, the removal rate of aromatic hydrocarbons can reach ≥98%, the removal rate of olefins can reach ≥96%, and the removal rate of metal ions can reach ≥99%.

[0037] Furthermore, the flow rate is 0.5-2 BV / h, preferably 0.5-1 BV / h, and more preferably 1 BV / h; the purpose of the slight negative pressure is to provide airflow power and improve the stability of adsorption, and it is preferably 0.05-0.1 MPa.

[0038] The following are preferred embodiments of the present invention. Unless otherwise specified, the reagents used are commonly used in the art, and the experimental methods used are those skilled in the art.

[0039] Example 1

[0040] 1) Preparation of modified activated carbon adsorbent: ①Pretreatment: Take 100g of activated carbon (specific surface area approximately 1007m²) 2 / g), pulverize to 30 mesh, wash 3 times with deionized water, and dry at 110℃ for 8 hours; ② In-situ growth of ZIF-8: Dissolve pretreated activated carbon, 8g Zn(NO3)2·6H2O and 20g 2-methylimidazole in 500mL methanol and disperse by ultrasonication for 30min; add 15g excess 2-methylimidazole and stir at 60℃ for 2h. ③ Covalent bonding of UiO-66-SO3H: Add 5g ZrCl4 and 7g 1,4-benzenedisulfonic acid to the system and heat-treat at 80℃ for 4h; ④ Post-treatment: After filtration, wash three times with methanol and dry at 80℃ for 6 hours to obtain modified activated carbon adsorbent with a BET specific surface area of ​​approximately 1211 m². 2 / g.

[0041] 2) Purification of n-octane: ①Pretreatment of the device: The modified activated carbon adsorbent described above is packed into a 15cm×2cm column and purged with nitrogen for 30min. ② Continuous purification: 500 mL of industrial-grade n-octane (containing 120 ppm benzene, 80 ppm ethylene, and 50 ppm Fe) 3+ (etc.) is introduced into the column at a flow rate of 1 BV / h, with the temperature controlled at 30℃ and the pressure at 0.08 MPa; ③ Product testing: ICP-MS and GC-FID tests showed that the removal rates of aromatic hydrocarbons (taking benzene as an example) and olefins (taking ethylene as an example) in the exported n-octane were 98.3%, 97.5%, and 99.0%-99.4%, with a purity of 99.993 wt%. Specific test results are shown in Tables 1 and 2 below.

[0042] Table 1: GC-FID Detection Results Test sample purity(%) Benzene (ppm) Ethylene (ppm) Industrial grade n-octane 95.0 120 80 Purified n-octane 99.993 2 2 Removal rate (%) / 98.3 97.5

[0043] Table 2: ICP-MS Detection Results metal ions Industrial grade n-octane (ppm) Purified n-octane (ppm) Removal rate (%) Na 200 2 99.0 Fe 50 0.35 99.3 Al 50 0.4 99.2 Mg 50 0.5 99.0 K 100 0.9 99.1 Ag 50 0.4 99.2 Cu 50 0.35 99.3 Mn 50 0.3 99.4

[0044] 3) Regeneration performance test:

[0045] The modified activated carbon adsorbent that was saturated with adsorption in Example 1 was regenerated:

[0046] ① Nitrogen purging: Introduce nitrogen at a flow rate of 4 BV / h and purge for 2 hours;

[0047] ② Vacuum thermal desorption: thermal desorption at 150℃ and 5kPa for 3 hours;

[0048] ③ Cyclic test: The purification-regeneration process was repeated 15 times, and the adsorption capacity decreased by 4.2%.

[0049] Example 2

[0050] 1) Preparation of modified activated carbon adsorbent:

[0051] ①Pretreatment: Take 100g of activated carbon (specific surface area 1195m²) 2 / g), pulverize to 30 mesh, wash 3 times with deionized water, and dry at 110℃ for 8 hours;

[0052] ② In-situ growth of ZIF-8: Pretreated activated carbon, 9g Zn(NO3)2·6H2O, and 22g 2-methylimidazole were dissolved in 500mL methanol and ultrasonically dispersed for 30min; 18g excess 2-methylimidazole was added and the mixture was stirred at 60℃ for 2h.

[0053] ③ Covalent bonding of UiO-66-SO3H: Add 10g ZrCl4 and 7g 1,4-benzenedisulfonic acid to the system and heat-treat at 80℃ for 4h.

[0054] ④ Post-treatment: After filtration, wash three times with methanol and dry at 80℃ for 6 hours to obtain modified activated carbon adsorbent with a BET specific surface area of ​​1406 m². 2 / g.

[0055] 2) Purification of n-octane

[0056] The purification method was the same as in Example 1, using the same batch of industrial-grade n-octane as the raw material. ICP-MS and GC-FID analysis showed that the removal rates of aromatic hydrocarbons (using benzene as an example) and olefins (using ethylene as an example) in the outlet n-octane were 99.17%, 98.13%, and 99.1%-99.6%, respectively, with a purity of 99.994 wt%. Specific test results are shown in Tables 3 and 4 below.

[0057] Table 3: GC-FID Detection Results Test sample purity(%) Benzene (ppm) Ethylene (ppm) Industrial grade n-octane 95.0 120 80 Purified n-octane 99.994 1 1.5 Removal rate (%) / 99.17 98.13

[0058] Table 4: ICP-MS Detection Results metal ions Industrial grade n-octane (ppm) Purified n-octane (ppm) Removal rate (%) Na 200 1.0 99.5 Fe 50 0.3 99.4 Al 50 0.4 99.2 Mg 50 0.4 99.2 K 100 0.9 99.1 Ag 50 0.3 99.4 Cu 50 0.3 99.4 Mn 50 0.2 99.6

[0059] 3) Regeneration performance test: The modified activated carbon adsorbent that was saturated with adsorption in this example was regenerated. ① Nitrogen purging: Introduce nitrogen at a flow rate of 5 BV / h and purge for 2 hours; ② Vacuum thermal desorption: thermal desorption at 150℃ and 3kPa for 3 hours; ③ Cyclic test: The purification-regeneration process was repeated 15 times, and the adsorption capacity decreased by 4.0%.

[0060] Example 3: Purification of high-impurity n-octane

[0061] 1) Preparation of modified activated carbon adsorbent: Same as in Example 2.

[0062] 2) Purification of n-octane:

[0063] ①Pretreatment of the device: The modified activated carbon adsorbent described above is packed into a 15cm×2cm column and purged with nitrogen for 30min.

[0064] ② Continuous purification: Add 500 mL of industrial-grade n-octane to be purified (containing 200 ppm benzene, 100 ppm ethylene, and 60 ppm Fe) 3+ (etc.) is introduced into the column at a flow rate of 1 BV / h, with the temperature controlled at 30℃ and the pressure at 0.08 MPa;

[0065] ③ Product Detection: ICP-MS and GC-FID tests showed that the removal rates of aromatic hydrocarbons (taking benzene as an example) and olefins (taking ethylene as an example) in the exported n-octane were 99.00%, 98.40%, and 99.1%-99.7%, with a purity of 99.993 wt%. Specific test results are shown in Tables 5 and 6 below.

[0066] Table 5: GC-FID Detection Results Test sample purity(%) Benzene (ppm) Ethylene (ppm) Industrial grade n-octane 95.0 200 100 Purified n-octane 99.993 2 1.6 Removal rate (%) / 99.00 98.40

[0067] Table 6: ICP-MS Detection Results metal ions Industrial grade n-octane (ppm) Purified n-octane (ppm) Removal rate (%) Na 200 1.0 99.5 Fe 60 0.3 99.5 Al 100 0.3 99.7 Mg 50 0.4 99.2 K 100 0.9 99.1 Ag 50 0.3 99.4 Cu 60 0.4 99.3 Mn 60 0.2 99.7

[0068] 3) Regeneration performance test of modified activated carbon adsorbent:

[0069] The modified activated carbon adsorbent that was saturated with adsorption in this embodiment was regenerated:

[0070] ① Nitrogen purging: Introduce nitrogen at a flow rate of 4 BV / h and purge for 2 hours;

[0071] ② Vacuum thermal desorption: thermal desorption at 150℃ and 5kPa vacuum for 3 hours;

[0072] ③ Cyclic test: The purification-regeneration process was repeated 15 times, and the adsorption capacity decreased by 4.5%.

[0073] Example 4: Purification of n-octane with high metal ion content

[0074] 1) Preparation of modified activated carbon adsorbent: The preparation method is the same as in Example 2.

[0075] 2) High-purity purification of n-octane:

[0076] ①Pretreatment of the device: The modified activated carbon adsorbent described above is packed into a 15cm×2cm column and purged with nitrogen for 30min.

[0077] ② Continuous purification: Add 500 mL of industrial-grade n-octane to be purified (containing 120 ppm benzene, 80 ppm ethylene, and 60 ppm Fe) 3+ (etc.) is introduced into the column at a flow rate of 1 BV / h, with the temperature controlled at 30℃ and the pressure at 0.08 MPa;

[0078] ③ Product testing: ICP-MS and GC-FID tests showed that the removal rates of aromatic hydrocarbons (taking benzene as an example) and olefins (taking ethylene as an example) in the exported n-octane were 99.17%, 98.13%, and 99.1%-99.7%, respectively, with a purity of 99.994 wt%. Specific test results are shown in Tables 7 and 8 below.

[0079] Table 7: GC-FID Detection Results Test sample purity(%) Benzene (ppm) Ethylene (ppm) Industrial grade n-octane 95.0 120 80 Purified n-octane (wt%) 99.994 1 1.5 Removal rate (%) / 99.17 98.13

[0080] Table 8: ICP-MS Detection Results metal ions Industrial grade n-octane (ppm) Purified n-octane (ppm) Removal rate (%) Na 200 1 99.5 Fe 60 0.2 99.7 Al 100 0.4 99.6 Mg 50 0.3 99.4 K 100 0.9 99.1 Ag 50 0.3 99.4 Cu 60 0.2 99.7 Mn 60 0.2 99.7

[0081] 3) Regeneration performance test of modified activated carbon adsorbent:

[0082] The modified activated carbon adsorbent that was saturated with adsorption in this embodiment was regenerated:

[0083] ① Nitrogen purging: Introduce nitrogen at a flow rate of 5 BV / h and purge for 2 hours;

[0084] ② Vacuum thermal desorption: thermal desorption at 150℃ and 2kPa for 3 hours;

[0085] ③ Cyclic test: The purification-regeneration process was repeated 18 times, and the adsorption capacity decreased by 4.7%.

[0086] Comparative Example 1: Purification of Single Activated Carbon

[0087] 1) Use unmodified activated carbon

[0088] 2) High-purity purification of n-octane:

[0089] ① Pretreatment of the apparatus: 100g of unmodified activated carbon (specific surface area 1400m²) is packed into a 15cm×2cm column. 2 / g), purge with nitrogen gas for 30 min;

[0090] ② Continuous purification: Add 500 mL of n-octane to be purified (same as in Example 1, containing 120 ppm benzene, 80 ppm ethylene, and 50 ppm Fe). 3+ The flow rate is 1 BV / h, and the temperature is controlled at 30℃ and the pressure at 0.08 MPa.

[0091] ③ Product Detection: According to the detection results of ICP-MS and GC-FID, the removal rate of aromatic hydrocarbons (taking benzene as an example) in the outlet n-octane is 75.00%, the removal rate of olefins (taking ethylene as an example) is 56.25%, and the removal rate of metal ions is between 40% and 80%, with a purity of 97.8 wt%. The specific detection results are shown in Tables 9 and 10 below.

[0092] Table 9: GC-FID Detection Results Test sample purity(%) Benzene (ppm) Ethylene (ppm) Industrial grade n-octane 95.0 120 80 Purified n-octane 97.8 30 35 Removal rate (%) / 75.00 56.25

[0093] Table 10: ICP-MS Detection Results metal ions Industrial grade n-octane (ppm) Comparative Example 1: High-purity n-octane (ppm) Removal rate (%) Na 200 40 80 Fe 50 20 60 Al 50 20 60 Mg 50 25 50 K 100 48 52 Ag 50 27 46 Cu 50 30 40 Mn 50 30 40

[0094] 3) Regeneration performance test:

[0095] The activated carbon in this comparative example that was saturated with adsorption was regenerated.

[0096] ① Nitrogen purging: Introduce nitrogen at a flow rate of 4 BV / h and purge for 2 hours;

[0097] ② Vacuum thermal desorption: thermal desorption at 150℃ and 5kPa for 3 hours;

[0098] ③ Cyclic test: The purification-regeneration process was repeated 15 times, and the adsorption capacity decreased by 25.3%.

[0099] Comparative Example 2: Preparation and purification of stepwise loaded adsorbents using physical methods

[0100] 1) Preparation of the adsorbent:

[0101] First, activated carbon is physically mixed and loaded with ZIF-8, dried, and then physically mixed and loaded with UiO-66-SO3H to obtain a stepwise loaded adsorbent.

[0102] 2) High-purity purification of n-octane:

[0103] ①Pretreatment of the apparatus: 100g of stepwise loaded adsorbent was loaded into a 15cm×2cm column and purged with nitrogen for 30min;

[0104] ② Continuous purification: Add 500 mL of industrial-grade n-octane to be purified (same as in Example 1, containing 120 ppm benzene, 80 ppm ethylene, and 50 ppm Fe). 3+ The flow rate is 1 BV / h, and the temperature is controlled at 30℃ and the pressure at 0.08 MPa.

[0105] ③ Product Detection: According to the detection results of ICP-MS and GC-FID, the removal rate of aromatic hydrocarbons (taking benzene as an example) in the exported n-octane is 91.67%, the removal rate of olefins (taking ethylene as an example) is 96.25%, and the removal rate of metal ions is between 68% and 90%, with a purity of 99.2 wt%. The specific detection results are shown in Tables 11 and 12 below.

[0106] Table 11: GC-FID Detection Results Test sample purity(%) Benzene (ppm) Ethylene (ppm) Industrial grade n-octane 95.0 120 80 Purified n-octane 99.2 10 3 Removal rate (%) / 91.67% 96.25%

[0107] Table 12: ICP-MS Detection Results metal ions Industrial grade n-octane (ppm) Purified n-octane (ppm) Removal rate (%) Na 200 20 90 Fe 50 10 80 Al 50 12 76 Mg 50 10 80 K 100 20 80 Ag 50 16 68 Cu 50 12 76 Mn 50 15 70

[0108] 3) Regeneration performance test:

[0109] The adsorbent that was saturated in this comparative example was regenerated:

[0110] ① Nitrogen purging: Introduce nitrogen at a flow rate of 4 BV / h and purge for 2 hours;

[0111] ② Vacuum thermal desorption: thermal desorption at 150℃ and 5kPa for 3 hours;

[0112] ③ Cyclic test: The purification-regeneration process was repeated 15 times, and the adsorption capacity decreased by 17.4%.

[0113] The performance of the above embodiments and comparative examples is summarized, and the results are shown in Table 13.

[0114] Table 13: Performance Comparison Results of Different Embodiments and Comparative Examples result Example 1 Example 2 Example 3 Example 4 Comparative Example 1 Comparative Example 2 <![CDATA[BET specific surface area (m 2 / g)]]> 1211 1406 1406 1406 / / High-purity n-octane (wt%) 99.993 99.994 99.993 99.994 97.8 99.2 Aromatic hydrocarbon removal rate (taking benzene as an example) 98.3 99.17 99.00 99.17 75.00 91.67 Olefin removal rate (taking ethylene as an example) 97.5 98.13 98.40 98.13 56.25 96.25 Metal ion removal rate (%) 99.0-99.4 99.1-99.6 99.1-99.7 99.1-99.7 40-80 68-90 Adsorption capacity decay (%) 4.2 4.0 4.5 4.7 25.3 17.4

[0115] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A modified activated carbon adsorbent, characterized in that, It is obtained by in-situ growth of ZIF-8 using activated carbon as a template, followed by covalent bonding with UiO-66-SO3H through heat treatment.

2. The method for preparing the modified activated carbon adsorbent according to claim 1, characterized in that, include: S1. Use activated carbon to remove impurities from the surface; S2. Disperse activated carbon, zinc source, and 2-methylimidazole into a solution, and then add excess 2-methylimidazole; React at 50-70℃ for 1-3 hours; S3. Add zirconium source and 1,4-benzenedisulfonic acid to the system obtained in S2, treat at 70-85℃ for 3-5 hours and then filter; S4. The filtered product is washed and dried to obtain a modified activated carbon adsorbent.

3. The preparation method according to claim 2, characterized in that, The activated carbon has a particle size of 20-40 mesh; and / or a specific surface area of ​​1000 m². 2 / g or more.

4. The preparation method according to claim 2, characterized in that, In step S2, during solution dispersion, the ratio of activated carbon, zinc source, and 2-methylimidazole used is 1g:(0.0002-0.0004)mol:(0.0015-0.003)mol. And / or, the solution uses an alcohol as a solvent; And / or, the excess amount of 2-methylimidazolium used is 3-5 times that of the zinc source.

5. The preparation method according to claim 2, characterized in that, The molar ratio of the zinc source to the zirconium source is (0.5-1.5):

1.

6. The preparation method according to claim 2, characterized in that, In step S3, the molar ratio of the zirconium source to 1,4-benzenedisulfonic acid is 1:(1.2-1.5).

7. The application of the modified activated carbon adsorbent according to claim 1 or the modified activated carbon adsorbent prepared by any one of claims 2-6 in the adsorption of impurities; wherein the impurities include at least one of aromatic hydrocarbons, olefins and metal ions.

8. The application according to claim 7, characterized in that, The application is for the preparation of high-purity n-octane.

9. The application according to claim 8, characterized in that, The application includes purifying and / or regenerating a modified activated carbon adsorbent, wherein the purification is performed by passing pure n-octane through the modified activated carbon adsorbent at a constant flow rate; and the regeneration is performed by first purging with nitrogen and then performing vacuum thermal desorption.

10. A method for preparing high-purity n-octane, comprising using the modified activated carbon adsorbent according to claim 1 or the modified activated carbon adsorbent prepared by any one of claims 2-6, characterized in that, The process involves introducing crude n-octane into an adsorption unit filled with the modified activated carbon adsorbent at a constant flow rate, controlling the temperature at 25-40℃, performing adsorption under a slight negative pressure, and collecting the adsorbed n-octane to obtain high-purity n-octane.